Impactos da implementação da norma NBR ISO 14001: estudo de caso em uma empresa potiguar - Cunha, Jalisson Marques da (Universidade Federal Rural do Semi-Árido, 2020)
There are currently diverse policies established to guide economic development without predatory consumption of the planet’s natural resources, as it was in the past of the world. One of the tools that aims to maintain this balance guiding the process of implementing an Environmental Management System (EMS), is the NBR ISO 14001. The present study aims to analyze the impacts caused by the certification of the ISO 14001 standard in a company in the state of Rio Grande do Norte. For this, it was necessary to list all certified companies in each Brazilian state, in order to map the existing certifications throughout the national territory, as well as the companies responsible for carrying out the certification. the as well as the companies responsible for carrying out the certification, in addition, the companies that are certified in the state were identified, and the company selected for this case study was selected. The results found show that in fact there is a relevant impact caused by certification.
Monografia
Keywords: Gestão ambiental; Empresa potiguar; NBR ISO 14001; Environmental management; Potiguar company; NBR ISO 14001; ENGENHARIAS::ENGENHARIA DE PRODUCAO